Depletable micro-layer for nucleate boiling simulations in micro-gravity conditions: A new approach. (July 2022) - Banerjee, Sandipan; Liu, Yang; Sussman, Mark; Lian, Yongsheng
Highlights: Develop a new model to calculate the effect of liquid micro layer on vapor bubble growth. Model the micro layer thickness change in microgravity condition. Simulation shows good agreement with experimental results. Abstract: Nucleate boiling constitutes high heat flux with considerably low wall-superheat. During nucleate boiling, the evaporation of a thin liquid layer trapped between the vapor bubble and the wall is a significant contributor to the bubble growth rate and heat-flux. Direct simulation of the thin liquid layer is challenging because its thickness is only a few micrometers. In this paper we proposed a new approach to simulate the liquid micro layer. In this approach we do not directly model the thin liquid layer but instead we calculate its contribution to vapor bubble growth by estimating the micro layer thickness at each time step and then integrating the temperature gradient across the thin triangular region to calculate the heat flux and the generated vapor volume. In addition, our approach models the thin layer depletion with an added evaporation term in the equation. The added term is able to model the reduction in the thickness of the microlayer. Results for nucleate boiling simulations under microgravity conditions are reported using the proposed micro layer approach in comparison with experiments performed on the International Space Station using perfluoro-n-hexane as the test liquid. Results for bubble growth rate, bubble shape and heat-flux are in good agreement with experiments and are verified with two different time-instants in the bubble life cycle.